Pengaruh Pemasaran Media Sosial, Brand Ambassador, Inovasi Produk Terhadap Keputusan Pengguna Melalui Citra Perusahaan pada Pengguna Byond by BSI - Gumilar Santika Atmaja; Deden Mulyana; Edy Suroso (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The aim of this study were to determine and to analyze the influence of social media marketing, Brand ambassador, and product innovation on the decision of BYOND users in Tasikmalaya through corporate image. The method used in this study was a survey with a descriptive quantitative approach. The sample size in this research was 390 nasabahts, selected through proportional random sampling. Data analysis used Partial Least Square-Structural Equation Modeling (PLS-SEM). The study found that social media marketing, Brand ambassador, product innovation, and corporate image had a positive and significant influence on the decision of BYOND users in Tasikmalaya. Social media marketing, Brand ambassador, and product innovation also had a positive and significant influence on corporate image. Furthermore, corporate image positively and significantly mediated the influence of social media marketing, Brand ambassador, and product innovation on the decision of BYOND users in Tasikmalaya. Therefore, the company needed to optimize its digital marketing strategy, collaboration with brand ambassadors, and product innovation supported by a positive corporate image to improve user decisions regarding BYOND.